تأثیر تمرینات خاصة لتطویر سرعة الاستجابة الحركیة لمهارة حائط الصد للاعبي الكرة الطائرة من وضع الجلوس - علي سبهان صخي; عمار خليل ابراهيم (الرياضة المعاصرة, 2016)
The opening words: - special exercises - speed of response to motor skill bulwark plane reel from a sitting position. A search on the four-door broken down as follows 1. A search on the simple introduction to the game of volleyball and the research problem and objectives of the research, which (to identify the effect of exercise training specific to the development of motor response to skill bulwark of volleyball players from sitting) speed mode and also the imposition of research (there are differences in women with significant differences between the results before and after the tests at the speed of the motor response and in favor of the post tests) also included a sample search on the (12) players out of 16 players for the national team. 2. ensure that the door presentation of the results of statistical processing using a set of tables, and then analyzed and discussed in a scientific manner accurate and supported by scientific sources through this discussion and then to reach the goals of the research and verification of the hypothesis. 3. Conclusion included the conclusions of which (the emergence of a positive effect of the exercises own installed in the section president of the modules, which focused on the development of kinetic response to skill bulwark Volleyball sit targeted by the study) and recommendations, including setting speed (the use of units of training varied and many contain exercises appropriate in the number of iterations contained therein and their proper regulation is consistent with the privacy of the skills of the game and the degree of difficulty).